Aestheticising rural poverty: representations of white working class youth in the documentary Rich Hill (2014). Issue 1 (2nd January 2018) - Keys, Wendy; Pini, Barbara
ABSTRACT: This paper examines representations of white rural working class youth in the award winning United States observational documentary Rich Hill (2014) through the lens of the aestheticisation of poverty. We begin the paper by establishing what we mean by the aestheticisation of poverty arguing it is a common trope in western culture which positions the poor as 'other' rendering them either invisible or as a failure. Following this, we situate our analysis within the literature on ethics in documentary film, examining debates which have inflected the release of other documentaries focused on the poor. In the next section we examine the film-makers' positionality revealing that while they foreground their historical connection to the town, they mute their middle-class subjectivity. The close textual analysis of the film in the subsequent parts of the paper detail the ways in which the film aestheticises poverty, that is via its particular visual style, sound/image relationship and deliberate focus on youth. Despite the director's intent the film does not challenge poverty but instead aestheticises it because it does not elaborate upon the complex factors which have given rise to the social problem that is rural poverty, and rendered it so intractable.